Inhibitory effect and related mechanism of decitabine combined with gemcitabine on proliferation of NK/T cell lymphoma cells - Lin, Lanke; Liu, Xiangqin; Yu, Hui; Deng, Huan; Peng, Kun; Chen, Jiang; Zhang, Chunle; Jiang, Tao; Liu, Xiaoqi (Frontiers in Pharmacology, 2023)
Background: EBV-associated lymphoma is a neoplasm with a poor prognosis, highly aggressive, and progressive rapidly. There is no standard clinical treatment protocol. Decitabine and gemcitabine are known to have anticancer properties against cells of various cancer, respectively. However, the effect of the combination medication on NK/T cell lymphoma cells and potential mechanisms have not been thoroughly investigated. Methods: Human NK/T cell lymphoma cells NK92MI were treated with decitabine and gemcitabine alone or in combination. Experiments, including the Cell Counting Kit-8 and flow cytometry, were performed to investigate how the combination of decitabine and gemcitabine affects the biological behavior of NK92MI cells in vitro. mRNA sequencing, RT-PCR, and western blotting were used to detect changes in the related signal pathway, mRNA, and protein expressions. Results: Decitabine and gemcitabine significantly inhibited the viability and proliferation of NK92MI cells in a dose-dependent manner. The combination index was less than 1 after treating with two drugs, which was a significant synergistic effect. The decitabine concentration with the best synergistic effect was 4.046µM, and the gemcitabine concentration was 0.005µM. Flow cytometry showed that combining two drugs could significantly promote apoptosis and arrest the cell cycle at the S phase. In the combined group, CASPASE3 protein levels were higher. KEGG, and PPI analysis showed differential genes were mainly related to cell proliferation, adhesion, and migration. RT-PCR and WB showed that the levels of HMOX1 and EBV cleavage gene BRLF1 were higher in the DAC and GEM combined group, while the protein and mRNA expression levels of SLC7A11 were lower than the others. In addition, the GPX4 protein expression level in the combination group was lower than that in the drug-alone group and the control group. In addition, the combination treatment increased the ROS level of NK92MI cells. Conclusion: Our current findings suggested that decitabine had an inhibitory effect on the proliferation of NK92MI cells when co-treated with gemcitabine. This combination may increase the expression of ferroptosis-related signaling molecules, thus inhibiting the proliferation of NK92MI cells. It also promoted apoptosis in NK/T cell lymphoma. For patients with NK/T cell lymphoma, this novel combination may provide clinical benefits.